Effective use of hydrogen sulfide and natural gas resources available in the Black Sea for hydrogen economy. (11th March 2021) - Ozturk, Merve; Midilli, Adnan; Dincer, Ibrahim
Abstract: In this article, we propose a novel system to effectively deploy an integrated fuel processing system for hydrogen sulfide and natural gas resources available in the Black Sea to be used for a quick transition to the hydrogen economy. In this regard, the proposed system utilizes offshore wind and offshore photovoltaic power plants to meet the electricity demand of the electrolyzer. A PEM electrolyzer unit generates hydrogen from hydrogen sulfide that is available in the Black Sea deep water. The generated hydrogen and sulfur gas from hydrogen sulfide are stored in high-pressure tanks for later use. Hydrogen is blended with natural gas, and the blend is utilized for industrial and residential applications. The investigated system is modeled with the Aspen Plus software, and hydrogen production, blending, and combustion processes are analyzed accordingly. With the hydrogen addition up to 20% in the blend, the carbon dioxide emissions of combustion decrease from 14.7 kmol/h to 11.7 kmol/h, when the annual cost of natural gas is reduced from 9 billion to 8.3 billion . The energy and exergy efficiencies for the combustion process are increased from 84% to 97% and from 62% to 72%, respectively by a 20% by volume hydrogen addition into natural gas. Highlights: Design and modeling of a novel system to generate hydrogen from hydrogen sulfide. Utilization of hydrogen sulfide and natural gas resources efficiently as obtained from the Black Sea. Investigation of hydrogen blending with natural gas for several applications. Studying the effects of hydrogen addition on the system performance.